Lesion correlates of secondary paroxysmal dyskinesia in multiple sclerosis - Fröhlich, Katharina; Winder, Klemens; Linker, Ralf; Huhn, Konstantin; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Schwab, Stefan; Seifert, Frank (Journal of Neurology, 2018)
Secondary paroxysmal dyskinesia is a rare but life-quality-compromising symptom in multiple sclerosis (MS) and might be associated with particular MS lesions. The present study intended to determine associations between paroxysmal dyskinesia and the MS-associated lesion site using a voxelwise lesion analysis. We conducted a retrospective study and sought MS patients with documented paroxysmal dyskinesia and controls without paroxysmal dyskinesia matched for age, disease severity, and disease duration in a local database. The MS lesions were analysed on T2-weighted magnetic resonance imaging scans (1.5 or 3 T), manually outlined, and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of paroxysmal dyskinesia voxelwise between patients with and without lesions in a given voxel using the Liebermeister test with 4000 permutations. From 15,869 MS patient records screened, we identified 25 patients with paroxysmal dyskinesia. The voxelwise analysis in 22 subjects yielded associations between paroxysmal dyskinesia and MS lesions in the internal capsule, the basal ganglia, and another prominent lesion cluster in the posterior periventricular white matter. Our voxelwise analysis shows associations between paroxysmal dyskinesia and MS lesions in the internal capsule and basal ganglia, areas contributing to motor sequence programming. This association in another lesion site located in the posterior thalamic radiation suggests that lesions in subcortical sensory pathways may also contribute to paroxysmal dyskinesia in MS.
EVALuna2:34912